2022
DOI: 10.3390/genes13061024
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis and Identification of a Female-Specific SSR Marker in Pistacia chinensis Based on Illumina Paired-End RNA Sequencing

Abstract: Pistacia chinensis Bunge (P. chinensis), a dioecious plant species, has been widely found in China. The female P. chinensis plants are more important than male plants in agricultural production, as their seeds can serve as an ideal feedstock for biodiesel. However, the sex of P. chinensis plants is hard to distinguish during the seedling stage due to the scarcity of available transcriptomic and genomic information. In this work, Illumina paired-end RNA sequencing assay was conducted to unravel the transcriptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Similarly, it was reported that a comparable number of unigenes were identified and annotated from the transcriptome study of P. chinensis (Choi et al 2019). However, the number of unigenes identified in this study was significantly lower than reports from the transcriptome studies of both P. vera (Karci et al 2020;Moazzzam Jazi et al 2017;Zeng et al 2019) and P. chinensis (Cheng et al 2022;Dong et al 2016). Since several other Pistacia species, including P. atlantica, P. lentiscus, and P. weinmannifolia, are also well known as valuable medicinal plants, it was thought that many genomic studies would have been conducted on these species.…”
Section: Transcriptome Analysis Of Pistacia Speciescontrasting
confidence: 39%
“…Similarly, it was reported that a comparable number of unigenes were identified and annotated from the transcriptome study of P. chinensis (Choi et al 2019). However, the number of unigenes identified in this study was significantly lower than reports from the transcriptome studies of both P. vera (Karci et al 2020;Moazzzam Jazi et al 2017;Zeng et al 2019) and P. chinensis (Cheng et al 2022;Dong et al 2016). Since several other Pistacia species, including P. atlantica, P. lentiscus, and P. weinmannifolia, are also well known as valuable medicinal plants, it was thought that many genomic studies would have been conducted on these species.…”
Section: Transcriptome Analysis Of Pistacia Speciescontrasting
confidence: 39%
“…In the present study, www.nature.com/scientificreports/ 2,510 SSR loci were identified from 37,538 unigenes in the A. heimuer transcriptome; the SSR frequency of 6.69% was higher than the rates for edible mushrooms such as Auricularia polytricha (4.70%) and Pleurotus eryngii (3.09%) 34,35 , indicating that the A. heimuer transcriptome contains abundant SSR loci. Factors such as database validity, species differences, and SSR search criteria may lead to differences in SSR frequency between A. heimuer and other analyzed species 36,37 . SSR repeat types differ among species, but the dinucleotide and trinucleotide repeat types are dominant 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Effective sex identification of female and male individual P. vera cultivars has been also achieved using Inter-Simple Sequence Repeat (ISSR) markers [24]. Sex-linked polymorphic EST-SSR markers were also effective in eliminating males in P. vera yet were not able to successfully identify the sex in other Pistacia species [6], except for the transcriptome-based EST-SSR marker identified by Chang et al [25], which was effective in distinguishing between male and female P. chinensis.…”
Section: Introductionmentioning
confidence: 99%